Four approaches to accounting for diversity in global organisations. (March 2016) - Özbilgin, Mustafa; Tatli, Ahu; Ipek, Gulce; Sameer, Mohammad
Abstract: This paper examines four distinct approaches to accounting for diversity outcomes in global organisations: shareholder, stakeholder, regulation and global value chain. Drawing on a study of 22 globally significant organisations, our analyses show that there is a need to move beyond narrow framing of benefits of diversity management based on shareholder and stakeholder perspectives. Our study demonstrates that regulation as well as global value chain is pertinent new perspectives that organisations need to move towards if they are to seriously account for diversity outcomes. Yet, our study shows that such a development is not likely to happen easily due to a number of significant challenges in accounting for diversity outcomes in global organisations.